The Agency of the Female Characters in Grimms’ and Garner’s Versions of “Cinderella” and “Snow White” - Lusiana Nur Annisa (Passage, 2017)
The present study examines the differences in the agency of the female characters in Grimms’ and Garner’s versions of the stories “Cinderella” and “Snow White”. In identifying the agency of the female characters, the study uses the indicator of actions based on Nealon Giroux’s (2003) and Schlosser’s (2015) conceptions of agency. The findings show that the agency of the female characters in Grimms’ and Garner’s versions of the stories differs in two aspects: the drive of the agency and the impact of the agency on the empowerment of the female characters. Despite the differences in depicting the female characters with their relations to the male characters, both versions of the stories cannot be considered feminist texts.Keywords: mid-pause, tight structured narrative, loose structured narrative, cognitive perspective